Biological activity and profiling of Salvia sclarea essential oil obtained by steam and hydrodistillation extraction methods via chemometrics tools - Aćimović, Milica G.; Cvetković, Mirjana T.; Stanković Jeremić, Jovana M.; Pezo, Lato L.; Varga, Ana O.; Čabarkapa, Ivana S.; Kiprovski, Biljana (Flavour and fragrance journal, 2022)
Salvia sclarea L. or clary sage is cultivated worldwide in temperate and sub‐tropical climates, as an ornamental and essential oil (EO) bearing plant. EO is obtained from fresh spikes in full flowering stage and is recognized as an important commercial product for food, beverage and cosmetic industries. This study investigated the EO composition of S. sclarea grown in Serbia (Southeast Europe) obtained by two different methods, steam (SD) and hydrodistillation (HD). GC‐MS analysis identified oxygenated monoterpenes as the main class of compounds for all EOs (between 81.8% and 88.2% depending on the distillation process). The most abundant oxygenated monoterpenes were linalyl acetate and linalool. In addition, in vitro antimicrobial (modified resazurin microtitre‐plate assay) and antioxidant activities (DPPH· assay) and total polyphenol content of obtained EOs were also evaluated. According to the assay used for the evaluation of the antibacterial activity, Gram‐negative bacteria were more sensitive to S. sclarea EO in comparison to Gram‐positive bacteria. EOs exhibited low antioxidant capacity, below 3% neutralized DPPH· radicals, reaching up to approximately 400 µg AAE mL‐1. This study also investigated a possibility for predicting retention indices (RIs) of compounds isolated from EOs. In total, 78 experimentally obtained RIs were applied to construct the prediction model. The quantitative structure‐chromatographic retention relationship (QSRR) model was used to anticipate the experimentally obtained RIs. Five molecular descriptors were selected by factor analysis and genetic algorithm to predict RIs. The obtained accuracy of the QSRR model reached r2 = .912, which showed that these models might be applied for predicting retention indices. Salvia sclarea essential oil is obtained by steam and hydrodistillation. GC‐MS was used for analysis of chemical composition. Total polyphenols content, antimicrobial and antioxidant activity were evaluated. QSRR model of retention time was developed.